THE EFFECT OF CORPORATE GOVERNANCE MECHANISMS AND ENVIRONMENTAL PERFORMANCE TO SUSTAINABILITY REPORTS - Fransiskus Xaverius TAW; Mudjilah Rahayu; Lindrawati Lindrawati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Sustainability report is a reporting tool that can be used by companies to achieve sustainability goals by measuring, and describing the environment, social and economic in a transparent manner. In order to achieve a good quality of sustainability report, it is necessary to have a corporate governance mechanism and environmental performance. The research purpose is to examine the effect of corporate governance mechanisms consists of commissioners council, managerial ownership, and audit committee, also environmental performance to sustainability report. The object of this research is the mining sector companies that at least once published a sustainability report and followed PROPER listed on the Indonesia Stock Exchange for the 2017-2020 period. The data obtained from annual reports and sustainability reports. The data analysis technique uses multiple linear regression analysis. The results of this study can be concluded that managerial ownership has a positive effect on sustainability reports. Meanwhile, the commissioners council, audit committee, and environmental performance have no effect on sustainability report.